Accuracy of anemia diagnosis by physical examination - Benseñor, Isabela Martins; Calich, Ana Luísa Garcia; Brunoni, André Russowsky; Espírito-Santo, Fábio Ferreira; Mancini, Renato Lendimuth; Drager, Luciano Ferreira; Lotufo, Paulo Andrade (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVES: Quantification of clinical signs such as the presence or absence of pallor at clinical examination is a key step for making diagnoses. The aim was, firstly, to evaluate two methods for anemia diagnosis by physical examination: four-level evaluation (crosses method: +/++/+++/++++) and estimated hemoglobin values, both performed by medical students and staff physicians; and secondly, to investigate whether there was any improvement in assessment accuracy according to the number of years in clinical practice. DESIGN AND SETTING: Forty-four randomly selected physicians and medical students in a tertiary care teaching hospital completed a physical examination on five patients with mild to severe anemia. METHODS: The observers used four-level evaluation and also predicted the hemoglobin level. Both methods were compared with the real hemoglobin value as the gold standard. RESULTS: The mean estimated hemoglobin value correlated better with the real hemoglobin values than did the four-level evaluation method, for attending physicians, residents and students (Spearman’s correlation coefficients, respectively: 1.0, 1.0 and 0.9 for guessed hemoglobin and -0.8, -0.8 and -0.7 for the four-level evaluation method). There were no differences in the mean “guessed” hemoglobin values from attending physicians, residents and students. However, the correlation between guessed hemoglobin value and the four-level method was positive for attending physicians, thus suggesting some kind of improvement with time (p = 0.04). CONCLUSIONS: This study showed that estimated hemoglobin was more accurate than evaluation by the four-level method. The number of years in clinical practice did not improve the accuracy of clinical examination for anemia.